In Marx's Shadow : Knowledge, Power, and Intellectuals in Eastern Europe and Russia. - Bradatan, Costica (Rowman & Littlefield Pub. Group, 2010)
Despite its key role in the intellectual shaping of state socialism, Communist ideas are often dismissed as mere propaganda or as a rhetorical exercise aimed at advancing socialist intellectuals on their way to power. By drawing attention to unknown and unexplored areas, trends and ways of thinking under socialism, the volume examines Eastern Europe and Russian histories of intellectual movements inspired - negatively as well as positively - by Communist arguments and dogmas. Through an interdisciplinarydialogue, the collection demonstrates how various bodies of theoretical knowledge (philosop.